2015
DOI: 10.1080/17470919.2014.994786
|View full text |Cite
|
Sign up to set email alerts
|

Studying the neurobiology of human social interaction: Making the case for ecological validity

Abstract: With this commentary we make the case for an increased focus on the ecological validity of the measures used to assess aspects of human social functioning. Impairments in social functioning are seen in many types of psychopathology, negatively affecting the lives of psychiatric patients and those around them. Yet the neurobiology underlying abnormal social interaction remains unclear. As an example of human social neuroscience research with relevance to biological psychiatry and clinical psychopharmacology, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 94 publications
0
9
0
1
Order By: Relevance
“…Moment-to-moment agreement between the perceiver and target can then be used to generate an objective empirical accuracy measure for the perceiver. These paradigms require the perceiver to use facial expressions, verbal content, vocal tone, posture, and other non-verbal cues to continuously track changes in emotional intensity, which closely mimics the skills needed in real-life social situations and requires coordination of abilities particularly tied to cognitive empathy (36,37). Empirical empathic accuracy measures are an important addition to empathy research as they have been shown to be reliable, can be applied in a variety of contexts, do not correlate particularly strongly with self-report measures and are more predictive of life outcome measures (38).…”
Section: Introductionmentioning
confidence: 99%
“…Moment-to-moment agreement between the perceiver and target can then be used to generate an objective empirical accuracy measure for the perceiver. These paradigms require the perceiver to use facial expressions, verbal content, vocal tone, posture, and other non-verbal cues to continuously track changes in emotional intensity, which closely mimics the skills needed in real-life social situations and requires coordination of abilities particularly tied to cognitive empathy (36,37). Empirical empathic accuracy measures are an important addition to empathy research as they have been shown to be reliable, can be applied in a variety of contexts, do not correlate particularly strongly with self-report measures and are more predictive of life outcome measures (38).…”
Section: Introductionmentioning
confidence: 99%
“…The first, and perhaps most obvious asset offered by this technology, is that it allows the generation of life-like simulations of social information. As noted by [15], the stimuli that are used in many social neuroscience studies lack important aspects of actual live social interaction; this concern is shared by other authors [72,73,74,75]. On the other hand, the use of unnaturalistic stimuli is necessary in order to exert control on potential extraneous variables, which would be difficult or impossible to control in field or natural experiments.…”
Section: Enhancing Social Neuroscience Protocols With Virtual Envimentioning
confidence: 99%
“…One aim of neuroscience is to gain further insight into how the human mind functions in everyday life. Yet, little is known about the link between neural activation and psychological experience outside the lab ( Eisenberger et al, 2007 ; Hogenelst et al, 2015 ). This is due to the local constraints of neuroscience methodology, especially fMRI, confining its use to the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the construct of interest is assessed only via psychological and neural processes in the laboratory and not as part of ongoing daily experience. High ecological validity is achieved when a measurement closely represents the usual conditions under which the process of interest occurs ( Hogenelst et al, 2015 ). The first step towards improving ecological validity is the development of naturalistic paradigms.…”
Section: Introductionmentioning
confidence: 99%